IMAGES OF UREUM LEVELS IN PATIENTS WITH LUNGER TUBERCULOSIS WHO ARE UNDERING INTENSIVE PHASE TREATMENT IN PUSKESMAS, NORTH CITY: Doi: https://doi.org/10.47918/jhts.v3i1.334 - Yusri Halada; Astria Lolo; Zakaria, Meyvita (Jurnal Ilmiah dr. Aloei Saboe, 2021)
Tuberculosis cases in Gorontalo city have reached 732 cases. Treatment of tuberculosis patients by applying antibiotics which are thought to have side effects on the kidney organs. One such antibiotic is rifampin which causes essential nephritis or inflammation of the kidneys. The purpose of this study was to describe urea levels in tuberculosis patients undergoing intensive phase treatment. The research method is quantitative descriptive research. The population was 45 people with pulmonary tuberculosis who underwent intensive phase treatment at Puskesmas Kota Utara, with a total sample of 10 people. The data analysis technique was processed through the IBM SPSS V 25.0 program. The results showed that urea levels of pulmonary tuberculosis patients were 80.0% normal and 20% increased. It was concluded that the urea level of tuberculosis patients who underwent intensive phase treatment had increased, not due to the consumption of OAT but due to external factors. It is recommended that patients with pulmonary tuberculosis check the level of urea after undergoing treatment, especially patients with elderly people. Tuberculosis cases in Gorontalo city have reached 732 cases. Treatment of tuberculosis patients by applying antibiotics which are thought to have side effects on the kidney organs. One such antibiotic is rifampin which causes essential nephritis or inflammation of the kidneys. The purpose of this study was to describe urea levels in tuberculosis patients undergoing intensive phase treatment. The research method is quantitative descriptive research. The population was 45 people with pulmonary tuberculosis who underwent intensive phase treatment at Puskesmas Kota Utara, with a total sample of 10 people. The data analysis technique was processed through the IBM SPSS V 25.0 program. The results showed that urea levels of pulmonary tuberculosis patients were 80.0% normal and 20% increased. It was concluded that the urea level of tuberculosis patients who underwent intensive phase treatment had increased, not due to the consumption of OAT but due to external factors. It is recommended that patients with pulmonary tuberculosis check the level of urea after undergoing treatment, especially patients with elderly people.